Supervisors’ Feedback in the TESL Practicum as Perceived by Student-teachers: A Case Study in A Malaysian Teacher Education Institute (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
The purpose of this research study was to investigate the perceptions of supervisory feedback of student-teachers involved in the teaching practicum in a Malaysian Teacher Education Institute. The sample, which was conveniently selected based on student-teachers’ interest and availability, consisted of 24 student-teachers from the Teacher Education Institute. Data were obtained by means of questionnaire. Data were analyzed qualitatively. After considering the perceptions of the student-teachers participating in this study, the findings suggested a characterisation of supervisory feedback that contributed to deepen the existing knowledge about feedback in the teaching practicum context. It enables to shed more lights into the areas of second language teaching in the classroom as the findings would be able to provide more support for future management and development of teacher education in Malaysia.